Anti-corruption agenda of the G20: Bringing order without law - Tanu M. Goyal (Indian Council for Research on International Economic Relations (ICRIER), 2020)
The G20 has emerged as a premier deliberative forum, involving leaders of some of the largest, systematically important countries of the world. Over the years, the G20 agenda has evolved to include pertinent issues for both developed countries and the emerging market economies. After the G20 Summits were launched, certain global concerns that required collective action became permanent features of the G20 agenda. Tackling corruption was one of them. Corruption is being characterised as an international problem requiring collective corrective action. The G20 established an Anti-Corruption Working Group as early as in 2010, at the fourth summit in Toronto, which sets the Anti-Corruption Action Plan for the G20 members. Over the years, the issues under the Working Group have evolved to capture continuous and emerging challenges for the G20 members. India has been actively involved in the anti-corruption agenda of the G20 and has periodically submitted its implementation reports to the G20. More recently, India has also contributed to the anti-corruption agenda by making suggestion on significant issues for G20 members. This paper discusses the evolution of the anti-corruption agenda globally and within the G20, and India's progress and contribution in furthering this agenda. While the objective of this paper is to report the progress of the G20 members including India, the paper also makes observations regarding the G20 as a multilateral body for addressing anti-corruption issues. The paper is based on a review of the G20 documents and discussions with experts in the area.
Keywords: F53; F55; N40; D73; D78; 330; corruption; global governance; G20; international institutions